Improvement of nutritional status after parathyroidectomy in patients receiving maintenance hemodialysis - Disthabanchong, Sinee; Saeseow, Sarunya; Khunapornphairote, Sirote; Suvikapakornkul, Ronnarat; Wasutit, Yodying; Tungkeeratichai, Jumroon (Frontiers in Medicine, 2023)
Aims/Introduction Parathyroidectomy is associated with improved survival in patients with end-stage kidney disease. Protein-energy wasting (PEW) is common in patients with kidney failure and predicts poor outcomes. Recent clinical trials have linked hyperparathyroidism to PEW. The present retrospective cohort study examined whether parathyroidectomy was associated with improvement in nutritional status in maintenance hemodialysis patients. Materials and methods One hundred twenty-nine maintenance hemodialysis patients who had successful parathyroidectomy during 2012–2018 were identified (PTX group) and matched 1:1 to 479 patients with parathyroid hormone (PTH) levels ≤1,000 pg./mL (non-PTX control group) and 187 patients with PTH levels >1,000 pg./mL (pre-PTX control group) by propensity score. The matchings yielded 120 matched pairs from PTX and non-PTX groups (cohort 1) and 76 matched pairs from PTX and pre-PTX groups (cohort 2). Baseline and follow-up nutritional parameters associated with PEW were compared over the 12-month study period. Results In cohort 1, substantially lower serum albumin and serum creatinine/body surface area (Cr/BSA) and higher proportions of patients with serum albumin ≤38 g/L (low albumin) and serum Cr/BSA ≤380 μmol/L/m2 (low Cr/BSA) were observed in the PTX group. These parameters improved significantly after parathyroidectomy. Total lymphocyte count (TLC) was comparable at baseline but the percentage of patients with TLC <800 cells/mm3 (low TLC) decreased substantially after parathyroidectomy. At follow-up, serum albumin, serum Cr/BSA and proportions of patients with low albumin and Cr/BSA became comparable with the non-PTX control group. The percentage of patients with low TLC became lower in the PTX group. Mixed-models analysis confirmed significant differences in the changes in serum albumin, serum Cr/BSA, and proportions of patients with low albumin and TLC between the two groups. In cohort 2, nutritional parameters were comparable at baseline. At follow-up, serum Cr/BSA was higher and proportions of patients with body mass index ≤18.5 kg/m2, low TLC and low Cr/BSA were lower in the PTX group. Weight gain was more frequent and of greater magnitude in the PTX group in both cohorts. A substantial reduction in blood pressure was also observed in the PTX group. Conclusion Severe hyperparathyroidism was associated with nutritional impairment which improved considerably after parathyroidectomy.